Ultrahigh Room‐Temperature Photoluminescence from Few to Single Quintuple Layer Bi2Te3 Nanosheets. Issue 13 (11th April 2018) - Hussain, Naveed; Zhang, Qingyun; Lang, Jialiang; Zhang, Ruoyu; Muhammad, Murtaza; Huang, Kai; Cosseron De Villenoisy, Thibault; Ya, Huang; Karim, Altaf; Wu, Hui
Abstract: Owing to its narrow indirect bandgap, bulk bismuth telluride (Bi2 Te3 ) exhibits exceptionally low room‐temperature photoluminescence (PL). Consequently, it remains challenging to achieve promising optical and optoelectronic performance from Bi2 Te3 . Moreover, due to the lack of plasmonic materials and available modulation methods, it is challenging to effectively control the surface plasmon resonance intensities in the visible region. Herein, thickness‐dependent photoluminescence studies unveil ultrahigh (282‐fold) room‐temperature photoluminescence (visible) from 20 quintuple layer Bi2 Te3 nanosheets (NSs) compared to 200 quintuple layer NSs, attributable to a significant bandgap opening. Intriguingly, considerable photoluminescence quenching is observed beyond the thickness of 20 quintuple layer Bi2 Te3 . The PL emission is further optimized with reference to the number of quintuple layers, and the mechanism possibly responsible for such PL behavior is elucidated. Moreover, the thickness modulation is put forward as an effective strategy to control visible surface plasmon resonance energy modes and their intensities. Bi2 Te3 nanosheets with large area and high crystallinity are fabricated on various silicon substrates by a facile hot‐pressing strategy, which facilitates investigation of intrinsic properties of 2D Bi2 Te3 . It is believed that these findings hold paramount importance in understanding the optical response of Bi2 Te3 toward nanoscale variations and help build next‐generation transparent and flexible optoelectronic/plasmonic devices. Abstract : Thickness‐dependent ultrahigh (282‐fold) room‐temperature photoluminescence from 20 quintuple layer Bi2 Te3 nanosheets is observed, as compared to 200 quintuple layer, owing to quantum confinement‐induced opening and transition (indirect–direct) of the optical bandgap. Thickness modulation as an effective strategy to control visible surface plasmon resonance modes and their intensities at nanoscale is presented, which is crucial for building high‐performance Bi2 Te3 ‐based optoelectronic/plasmonic devices.